An analysis of the graduate models in Latin America - Garzón Félix, María Fernanda (2016)
The objective of this research was to propose a graduate model for sustainable human development after evaluating different trends of the existing models. We used theoretical methods such as the historical and logical methods, for analysing the evolution of the different graduate models; the analysis and synthesis method, for evaluating the data collected during the study; and the statistical and mathematical method, for processing the data and generating quantitative results. We carried out interviews with graduate students from The Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, Ecuador, and interviews with lecturers and university authorities for evaluating the management of the graduate models at the university and region. In the results, we established indicators for classifying the graduate models, which served to develop a proposal that meets the current needs of this process. The model begins with the consideration of the social needs in the area of study to promote the development of human potentials. We consider the importance of graduate programs in solving regional development problems in connection with sustainable human development